KEKUATAN HUKUM ACTA VAN DADING SEBAGAI HASIL KESEPAKATAN MEDIASI DALAM GUGATAN PERDATA - Triana Dewi Seroja; Ampuan Situmeang; Febri Jaya; Supardi (to-ra, 2020)
Mediation has been regulated in Paragraph 1 Article 1 PERMA no. 1 2016, which is related to the practice of judicial mediation. "Mediation is a way of resolving disputes through the negotiation process to reach an agreement between the parties with the involvement of an intermediary," said the article. The problem in this article is important because the parties can make a peace agreement before the judge who handles the case. In addition, it can be done outside the court which has become known as legal practice. Courts are a matter of peace. This study uses a normative legal approach. The results of the author's research show that the legality of the law that is decided by the judge in court and consensus causes the parties to try to resolve their disputes and must be forced to consider the peace case approved by the judge to be law and have legal force. Be irrefutable. If the settlement of a dispute outside the court is decided by a judge during the trial and arranged in a peaceful case, both parties are legally obliged to follow their decision. A peace dispute that has not been resolved by a judge's decision is poor law enforcement and one of the parties can continue to file lawsuits. Regarding the settlement mechanism between the parties or the mediator in the district court, the judge hears the peace agreement case and the judge strengthens the peace agreement with a peace agreement. Keywords: Legality, Lawsuit, Plea, Determination, Result of Mediation.